(untitled) (Conference on English Language Teaching, 2023)
The rapid development of the educational system in Indonesia is reflected in the growth of educational institutions. Relevant studies shown for the last ten years, parental decision in Indonesia tends to prefer private schools for their children to public ones with a rationale that teachers in private schools offer more quality. This study aims to investigate the language proficiency of the teachers in One Earth School, Denpasar Bali, based on the CEFR assessment framework and its relation to the ability of teachers in performing classroom language. This study employs a case study design with three teachers as the subjects. The teachers selected are those who fulfill the criteria to be subjects seen from its experience and actively engaged in professional development. The data are collected by utilizing several means such as speaking test proficiency with CEFR based assessment, document study, and field observation. This study is expected to give a contribution on empowering English teachers to engage in professional development and displaying a clear picture whether or not teachers with certain proficiency levels could successfully transform them in classroom language.